Prevalence, risk factors, and main characteristics of bruises in cattle: A meta-analysis in the American continent. - Sánchez-Perez, Jaime N.; Félix-Leyva, Briseyda J.; Velázquez, Diana Z.; Rosiles, José R.; Montero-Pardo, Arnulfo; Strappini, Ana Carolina; Gallo, Carmen; Robles-Estrada, Juan Carlos; Portillo-Loera, Jesús J.; Diaz, Daniel; Dávila-Ramos, Horacio (Veterinaria México OA, 2022)
Bruises threaten the welfare of cattle because they cause pain, suffering, and stress during the pre-slaughter stage. Thus, we used meta-analyses to estimate the prevalence of carcass bruising in cattle from the American continent, determined the characteristics of the bruises, and calculated the odds ratio (OR) of risk factor categories associated with bruising. We searched electronic databases to retrieve primary studies conducted in the American continent, which reported cattle carcass bruising, analyzed the size, location, shape, and age of the bruises, and assessed risk factors for bruising. We included 46 studies from nine countries comprising 928 447 cattle carcasses with an overall prevalence of 59.5 % (95 % CI: 51.9-66-9) and 2.9 (range 3.4-7.4) bruises per carcass in average. The prevalence doubled from 30.7 % during 1991-2000 to 64.2 % during 2011-2020. Fresh, small-sized bruises of the lowest severity and located mainly in the hindquarter were highly prevalent (37.5-66.4 %). The removed meat due to bruising ranged 0.11-1.12 kg/ carcass with an accumulated weight of condemned meat between 15.6647 kg. Among intrinsic factors, older cattle, dairy cattle, and female cattle had greater odds of bruising (OR= 1.57-1.98). For extrinsic factors, the odds for bruising increased 1.4-2.2 in cattle sourced from auction markets and exposed to poor handling, suboptimal transportation conditions, and deficient facilities. In cattle from America, bruises are a concern because their prevalence is growing and 60 % of cattle assessed in the studies suffered a bruise. Improving facilities and transportation conditions together with proper training of the personnel during the handling and transportation of the cattle will reduce bruising incidence.